Emoji Based Marketing And Consumer Engagement: A Systematic Literature Review Of Recent Studies (2022–2026) - Chairunnisaa M Z Huzaen (International Journal of Economics and Development, 2026)
The growing use of emojis in digital communication has transformed the way brands interact with consumers and has increased scholarly interest in emoji-based marketing. However, existing studies remain fragmented across different contexts and outcomes, and limited attention has been devoted to providing an integrated understanding of how emoji-based communication contributes to consumer engagement. Therefore, this study aims to synthesize existing knowledge on emoji-based marketing and consumer engagement through a Systematic Literature Review (SLR). The review followed the PRISMA 2020 framework and utilized the Scopus database to identify relevant studies published between 2022 and 2026. An initial search yielded 30 records, of which 20 articles were retained after the screening and eligibility assessment processes. The selected studies were analyzed using thematic analysis to identify major themes, research trends, and future research opportunities. The findings reveal that the dominant themes in the literature include emoji-based communication in digital marketing, consumer engagement, and consumer outcomes associated with emoji usage. Emojis have evolved from simple visual symbols into strategic communication tools that enhance emotional appeal, interaction, and message effectiveness, thereby contributing to trust, brand attitudes, purchase intentions, electronic word-of-mouth, and brand loyalty. The review also identifies several emerging topics, including AI-assisted communication, social commerce, virtual consumer interactions, and other evolving digital environments. By integrating insights from multiple theoretical perspectives, this study contributes to the consumer engagement literature by providing a comprehensive understanding of the mechanisms through which emoji-based communication influences consumer engagement and relationship building. Furthermore, the review identifies theoretical, contextual, and methodological gaps that offer promising directions for future research and provides practical implications for marketers seeking to strengthen brand–consumer relationships in digital environments.